The importance of volatility in inflow in a deregulated hydro-dominated power market - Torstein Bye; Annegrete Bruvoll; Finn Roar Aune (Statistics Norway, Research Department, 2006)
In 2002/2003, the Nordic hydro-dominated power market faced a short-term supply shock. In autumn, precipitation and inflow were unusually low. As a result, there were record high prices in the following winter. Questions were raised whether the deregulated market creates sufficient incentives to invest in new production and transmission capacity to secure supply when overall inflow fails. One fear is that the market could break down when precipitation and inflow fails during the whole year, which is more probable than a short-term extreme inflow failure. We apply a market model to simulate the market effects with two events: i) an overall inflow shortage 25 per cent lower than normal, and ii) a seasonally biased inflow shortage, as happened in 2002/03. The 25 per cent low inflow scenario shows that significantly higher price effects are likely to occur in the Nordic power market in the future than in the past. However, the price effects are less than one would expect when compared to 2002/03, but prices remain higher for a longer period of time. The simulations do not indicate any problems in the functioning of the market within these scenarios.
Keywords: C61; D41; Q41; 330; Volatile power markets; deregulated power markets; security of supply